Comparative Analysis of Student’s Learning Motivation Constantly in Blooket Learning Media and Question Card Media at State Elementary School - Putri Berliana Nurindah; Abdul Karim; Nur Asyiah (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This research is motivated by the low learning motivation of students in the learning process which is still dominated by conventional methods, making students quickly bored, less enthusiastic, and less active. To overcome this problem, innovative, interesting learning media are needed, and are able to increase student motivation. This study aims to determine the differences in learning motivation of fourth-grade students of State Elementary School 1 Arjawinangun using digital gamification-based learning media Blooket and question card media. This study uses a quantitative approach with a quasi-experimental design of the Nonequivalent Control Group Design type, involving 70 fourth-grade students (35 per group). Data were collected through questionnaires, observations, and documentation, where student learning motivation was measured using a validated 24-item Likert scale questionnaire. Data analysis was carried out by testing validity, reliability, normality, homogeneity, t-test, and N-Gain test using SPSS version 27. The results showed that there were significant differences between the experimental group using Blooket media and the control group using conventional question card media. The t-test results showed a significant difference (p < 0.001, t = 3.793), where the experimental class with Blooket media obtained a higher increase in learning motivation compared to the control class. Thus, it can be concluded that the use of digital gamification-based learning media, especially Blooket, is more effective than question card media in increasing the learning motivation of fourth-grade students at State Elementary School 1 Arjawinangun. This finding provides practical implications that educators should prioritize the use of digital gamification learning tools as a strategy to increase student learning motivation, especially in the context of social studies learning in elementary schools.